2016
DOI: 10.1002/1873-3468.12486
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic landscape of human papillomavirus 16 E6‐regulated gene expression and splicing events

Abstract: The oncoprotein E6 of high-risk human papillomavirus (HPV) is responsible for the initiation and progression of cervical cancer. In the present study, we performed RNA-sequencing analysis in HPV16 E6-expressing 293T cells and identified 56 differentially expressed genes (DEGs) and a number of cellular pathways significantly affected. We confirmed nine of these DEGs in both cell models and clinical tissue samples. Furthermore, we performed de novo transcriptome assembly of 1128 novel human transcripts and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Several years later, another group demonstrated the splicing capabilities of HPV16 E6 overexpression in HPV-negative cells [ 103 ]. The changes to the transcriptome and splicing profile were compared upon the transient overexpression of HPV16 E6, and validated in clinical tissue samples.…”
Section: Mechanism Of E6 and E7 Regulating Cellular Pathwaysmentioning
confidence: 99%
“…Several years later, another group demonstrated the splicing capabilities of HPV16 E6 overexpression in HPV-negative cells [ 103 ]. The changes to the transcriptome and splicing profile were compared upon the transient overexpression of HPV16 E6, and validated in clinical tissue samples.…”
Section: Mechanism Of E6 and E7 Regulating Cellular Pathwaysmentioning
confidence: 99%
“…The spectrum of signaling pathways reprogrammed in the "host" cell (keratinocyte) under the influence of HPV oncogenes E6 and E7 and depending on the life cycle of HPV (productive or unproductive, transforming infection) has been characterized [14] Spontaneously immortalized neonatal epidermal keratinocytes (NIKS) [15] Primary normal epidermal keratinocytes (NHEKs) [16] SV40 Т-antigen-immortalized embryonic kidney cells (HEK293T) [17] hTERT-immortalized keratinocytes of the oral cavity (NOKs)…”
Section: Referencesmentioning
confidence: 99%
“…Two studies have shown that CELF3 may play a role in cancer. The upregulation of CELF3 is reported to be induced by HPV16 E6 and is thought to be crucial for downstream RNA splicing changes, such as exon skipping [94]. Furthermore, in patients with colorectal cancer metastasis, different patterns of expression and copy number variations are observed for CELF3.…”
Section: Other Celf Membersmentioning
confidence: 99%